Stent-assisted coiling of paraclinoid aneurysms: risks and effectiveness. (23rd August 2010) - Ogilvy, Christopher S; Natarajan, Sabareesh K; Jahshan, Shady; Karmon, Yuval; Yang, Xinyu; Snyder, Kenneth V; Hopkins, L Nelson; Siddiqui, Adnan H; Levy, Elad I
Abstract : Background: Stent assistance for treatment of wide-based aneurysms is becoming rapidly accepted. Methods: Cases of aneurysms arising in the paraclinoid location of the internal carotid artery treated with intracranial stents and/or bare platinum coils were analyzed retrospectively from our prospectively collected database. We identified 70 aneurysms treated with stent assistance (including one stenting-alone case) and 24 aneurysms treated with coiling alone. Stenting-assisted coiling was achieved either as a one-time treatment or as a two-step maneuver with the stent placed several weeks before coiling, or stent-assisted coiling was used as a second maneuver in aneurysms that recanalized after previous coiling. Results: In aneurysms treated with stent assistance, 60% had ≥95% occlusion at treatment completion, a result comparing favorably with the 54.2% rate of ≥95% occlusion associated with coiling alone. At last follow-up, 60 aneurysms treated with stent assistance had a 66.7% incidence of ≥95% occlusion, with no in-stent stenosis; 75% of patients treated with coiling alone had ≥95% aneurysm occlusion. Thrombus occurred during stent deployment in two patients, one with and one without neurologic sequelae; stent displacement occurred in one patient without neurologic sequelae. At last follow-up, 57 of 62 patients (91.9%) treated with stent-assisted coiling experienced excellent/good outcomes (modified Rankin scale score ≤2). These results compared favorably with those for the coiling-alone group in which 23 of 24 (95.8%) had good outcomes. Conclusion: Stent-assisted coiling of paraclinoid aneurysms did not add significantly to morbidity; overall effectiveness was comparable to that of bare coiling of paraclinoid aneurysms. These results require confirmation by a prospective controlled trial.